Exploring University Students’ Listening Self-Efficacy and Its Role in Oral Fluency Development - Nofry Frans; Vera Wahani (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2026)
The findings of this study revealed distinct differences between fourth- and sixth-semester students in how they processed listening activities and how these differences influenced their oral fluency. Fourth-semester students often relied on word-by-word comprehension and mental translation, which led to stress, hesitations, and disrupted speech flow. In contrast, sixth-semester students demonstrated meaning-focused listening strategies, enabling quicker responses, more structured discourse, and enhanced fluency. Observations and documentation further confirmed that greater exposure to authentic listening materials contributed to more stable speech rhythm, sustained continuity, and heightened confidence in oral production. The main practical implication of this study is that English language educators should place stronger pedagogical emphasis on authentic listening practice and meaning-oriented strategies rather than word-for-word comprehension. By designing classroom activities that encourage students to focus on main ideas, process listening input more efficiently, and build confidence in their listening abilities, educators can directly reduce students’ anxiety and foster more stable oral fluency. This contribution is significant because it provides a clear instructional pathway: improving listening experiences not only enhances comprehension but also builds psychological readiness and communicative competence, which are essential for success in higher education language learning contexts.